PERAN NOTARIS PEMBUAT AKTA KOPERASI DALAM PENCEGAHAN PRAKTIK PINJAMAN ONLINE ILEGAL - Raissa Aprilita Limbong; Mohammad Fajri Mekka Putra (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIH Awang Long, 2022)
This Paper aims to explore the role of Notary to preventing the practice of Illegal Online Loans. The Cooperative Deed Maker Notary (NPAK) has a role preventing Illegal Loans through the stages of establishing a Cooperative Legal Entity. In practice, Illegal Online Lenders usually use the status as a Savings and Loan Cooperatives on its establishment. Many party who misuse it and against some of the rules based on the establishment of a Cooperative based on Law no. 25 of 1992 concerning Cooperatives. Authority of a Notary under the Law on Notary Positions (